Coexisting pulmonary haemorrhage and venous thrombosis: a tricky but novel case. (20th October 2016) - Fielding, Alexandra; Pecheva, Mira; Farghal, Aser; Phillips, Russell
Abstract : We present a case of Lemierre's disease complicated by pulmonary artery pseudoaneurysm. A previously well woman aged 43 years presented with a history of a sore throat and worsening dyspnoea. She was diagnosed with a severe cavitating bilateral pneumonia complicated by internal jugular vein thrombosis consistent with a diagnosis of Lemierre's disease. She had an episode of massive haemoptysis which was confirmed to be due to a pulmonary artery pseudoaneurysm which required radiologically guided embolisation. She then required surgical decortication for bilateral empyemata. Blood cultures revealed growth of Slackia exigua, an organism yet to be linked with both of these complications concurrently. We believe this to be a novel case of this bacterium causing thrombosis and haemorrhage.